2015
DOI: 10.4103/0019-5154.156376
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous acroangiodermatitis

Abstract: Acroangiodermatitis is a rare self-limited angioproliferative lesion which can be associated with congenital vascular malformations or acquired venous insufficiency. Despite of its benign character, differential diagnosis of this lesion is very important because it closely resembles Kaposi sarcoma. Here we present a 26-year-old male patient with unilateral, purplish-red colored papules on his right ankle which diagnosed as acroangiodermatitis and discuss histopathological features, differential diagnosis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“… 12 , 13 This is generally thought to be a reactive process secondary to ischemia, leading to an intra‐ or extra‐vascular lobular or diffuse proliferation of endothelial cells and pericytes 12 , 13 A variant of this condition, acroangiodermatitis, occurs secondary to stasis dermatitis, and is noted to also have a lobular architecture. 14 Another subtype, “diffuse dermal angiomatosis,” may present in the setting of large pendulous breasts. Despite the similarity in location, this entity typically has a more diffuse and interstitial vascular growth pattern rather than the distinctly nodular architecture seen in our cases.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 This is generally thought to be a reactive process secondary to ischemia, leading to an intra‐ or extra‐vascular lobular or diffuse proliferation of endothelial cells and pericytes 12 , 13 A variant of this condition, acroangiodermatitis, occurs secondary to stasis dermatitis, and is noted to also have a lobular architecture. 14 Another subtype, “diffuse dermal angiomatosis,” may present in the setting of large pendulous breasts. Despite the similarity in location, this entity typically has a more diffuse and interstitial vascular growth pattern rather than the distinctly nodular architecture seen in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…A differential diagnosis should be made to differentiate AAD from other conditions, such as Kaposi's sarcoma, vasculitis, actinic keratosis, stasis dermatitis, hemangiomas, lymphangiomas, and lymphangiosarcomas (7,8). It must be remarked that, in rare cases, AAD develops in patients presenting no CVI or any underlying AVMs (7,(9)(10)(11). The pathological examination showed that there was intradermal capillary proliferation as small nodules with perivascular inflammation underlying the fibrous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In Pseudo-Kaposi's sarcoma, CD34 is positive in endothelial cells; however, it is negative in Kaposi's sarcoma (6). Pseudo-Kaposi's sarcoma and Kaposi's sarcoma have similar histopathological features; therefore, Pseudo-Kaposi's sarcoma is often clinically misdiagnosed as Kaposi's sarcoma (9).…”
Section: Discussionmentioning
confidence: 99%